Effect of non-pharmacological interventions for overweight/obese women with polycystic ovary syndrome on ovulation and pregnancy outcomes: a protocol for a systematic review and network meta-analysis - Juan Li; Jie Yang; Fan-rong Liang; Jun Zhou; Gui-Xing Xu; Han Yang; Yan-qun Xiao; Jia-jia Liu; Zhi-yong Xiao; Xiao-yan Zheng; Li-ying Liu; Zheng Yu (BMJ Open)
Introduction Most overweight/obese women with polycystic ovary syndrome (PCOS) have infertility issues which are difficult to treat. Non-pharmacological interventions used for the management of infertility include lifestyle interventions, acupuncture therapies and nutritional supplements. These interventions have been reported to be beneficial in alleviating infertility among overweight women with PCOS. However, effect and safety of these non-pharmacological interventions vary, and there is no standard method of clinical application. Therefore, it is necessary to conduct a systematic review and network meta-analysis (NMA) to rank these non-pharmacological interventions in terms of effect and determine which one is more effective for clinical application.Methods and analysis We will retrieve eight databases including Cochrane Library, Medline, Embase, PsycINFO, Chinese National Knowledge Infrastructure, WanFang Data, the Chongqing VIP Database and China Biology Medicine disc from their inceptions onwards. In addition, four clinical trial registries and the related references will be manually retrieved. The primary outcome will be clinical pregnancy. Live birth, ovulation, pregnancy loss, multiple pregnancy and adverse events related to interventions will be considered as the secondary outcomes. STATA software V.15.0 and Aggregate Data Drug Information System V.1.16.8 will be used to conduct pairwise meta-analysis and NMA. The Grading of Recommendations Assessment, Development and Evaluation system will be adopted to evaluate the certainty of evidence.Ethics and dissemination Ethical approval will not be required because the study will not include the original information of participants. The results will be published in a peer-reviewed journal or disseminated in relevant conferences.PROSPERO registration number CRD42021283110.